2016
DOI: 10.1186/s13068-016-0581-3
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the microbiome of a thermophilic biogas plant by metagenome and metatranscriptome analysis complemented by characterization of bacterial and archaeal isolates

Abstract: BackgroundOne of the most promising technologies to sustainably produce energy and to mitigate greenhouse gas emissions from combustion of fossil energy carriers is the anaerobic digestion and biomethanation of organic raw material and waste towards biogas by highly diverse microbial consortia. In this context, the microbial systems ecology of thermophilic industrial-scale biogas plants is poorly understood.ResultsThe microbial community structure of an exemplary thermophilic biogas plant was analyzed by a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 90 publications
(132 reference statements)
4
91
0
3
Order By: Relevance
“…Figure modified according to Maus et al . (). Carbohydrates are labelled in light orange ovals, transporters in blue and corresponding genes in yellow rectangles.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure modified according to Maus et al . (). Carbohydrates are labelled in light orange ovals, transporters in blue and corresponding genes in yellow rectangles.…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, lactate could be used for pyruvate production. Hydrogen and acetate production is known for D. tunisiensis L3 and was previously discussed as hint for a syntrophic lifestyle with aceticlastic or hydrogenotrophic Archaea (Maus et al ., ; Stolze et al ., ). This assumption is further supported by the presence and partially high transcriptional activities of genes encoding enzymes associated with syntrophy (Worm et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defluviitoga spp. have been detected at high levels in other thermophilic digesters (Maus et al ., 2016b) indicating its potential significance to methane production at high temperatures. Notably, genera harbouring known syntrophic acetate‐oxidizing (SAO) bacteria of Tepidanaerobacter and Syntrophaceticus (Westerholm et al ., , ) were detected at higher rRNA and rRNA gene fractions in the codigesters compared to SS digesters, again with the exception of the thermophilic SS2T digester (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the process conditions, such as temperature and fed substrates, differences in the community profiles were identified [39][40][41]. For example, the bacterial phyla Actinobacteria, Deltaproteobacteria, and Spirochaetes were frequently found in mesophilic bioreactors [42], whereas members of the phylum Thermotogae (42%) were observed to be a predominant taxon under thermophilic conditions [1,43,44]. Comparison of the four biogas communities analyzed in this study revealed that the genera Defluviitoga and Halocella were highly abundant in the thermophilic BGP4.…”
Section: Discussionmentioning
confidence: 96%